Diabetes Mellitus Control and Chronic Kidney Disease (American Journal of Chemistry and Pharmacy, 2023)
Chronic kidney disease (CKD) is the rampant onset of diabetes and related complications; chronic kidney disorders and end-stage renal disease are progressing in more than 10% of the world population and mostly affect the elderly, women, minorities and patients with diabetes and hypersensitivity. The early stages of CKD are typically quiet; thus, many people are unaware they have the condition. Data for this review was gathered from Google Scholar, Scopus, PubMed, Elsevier, Cochrane, Sage, Medline, and Web of Science. Studies were selected from 2018-2023, using keywords such as Diabetes mellitus management, chronic kidney disease, microalbuminuria, target time in range, impaired fasting glucose, management ways, lifestyle modification, medication treatment, and diet control. Although blood glucose levels are too unpredictable to provide a reliable evaluation, measures reflecting long-term glycemic load are used instead. The results gathered after the review suggests that optimal glycemic control along with lifestyle medication and diet control contributes to better outcomes in individuals with DM, particularly for microvascular damage. While, HbA1c is the most well-known glycemic biomarker of long-term glycemic management. This suggests that effective treatments are progressing on progression.This review has discussed different CKD management parameters; the authors have discussed the disease’s treatment criteria and protocols, such as pharmacological therapies, lifestyle modifications, physical activities and insulin therapy and concluded that to avoid CKD, it’s critical to concentrate on underlying problems including hyperglycemia, hypertension, microalbuminuria, sedentary behaviour, and smoking. The occurrence of CKD can be reduced with changes in lifestyle, such as increased physical activity, nutritious food, and water consumption.